2021
DOI: 10.1186/s13075-021-02491-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of osteoclastogenesis by mast cell in rheumatoid arthritis

Abstract: Background In the pathogenesis of rheumatoid arthritis (RA), the role of mast cells has not been revealed clearly. We aimed to define the inflammatory and tissue-destructive roles of mast cells in rheumatoid arthritis (RA). Methods Serum and synovial fluid (SF) concentration levels of tryptase, chymase, and histamine were quantified using ELISA. After activating mast cells using IL-33, the production of TNF-α, IL-1β, IL-6, IL-17, RANKL, and MMPs wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…In synovial tissues, lymphocytes and synoviocytes produced excessive inflammatory cytokines, such as IL-6, IL-1β and TNF-α, leading to synovitis [ 47 ]. Furthermore, cytokine stimulated synoviocytes secreted MMP and receptor activator of nuclear factor kappa B ligand (RANKL) into SF and consequently lead to cartilage degradation and joint destruction [ 48 ]. The pathobiology progression of CIA rat model was similar to that in RA patients.…”
Section: Resultsmentioning
confidence: 99%
“…In synovial tissues, lymphocytes and synoviocytes produced excessive inflammatory cytokines, such as IL-6, IL-1β and TNF-α, leading to synovitis [ 47 ]. Furthermore, cytokine stimulated synoviocytes secreted MMP and receptor activator of nuclear factor kappa B ligand (RANKL) into SF and consequently lead to cartilage degradation and joint destruction [ 48 ]. The pathobiology progression of CIA rat model was similar to that in RA patients.…”
Section: Resultsmentioning
confidence: 99%
“…( 15 ) The results of the present study indicate for the first time that mast cells’ osteoclastogenic effects might also be mediated partly via RANKL. Indeed, mast cells were shown to release RANKL in the inflammatory conditions of atherosclerosis or rheumatoid arthritis ( 3,71 ) and after bone fracture. ( 15 )…”
Section: Discussionmentioning
confidence: 99%
“…(15) The results of the present study indicate for the first time that mast cells' osteoclastogenic effects might also be mediated partly via RANKL. Indeed, mast cells were shown to release RANKL in the inflammatory conditions of atherosclerosis or rheumatoid arthritis (3,71) and after bone fracture. (15) In the present study, we aimed to investigate the cross-talk between mast cells and osteoclasts in more detail and with more translational relevance.…”
Section: Discussionmentioning
confidence: 99%
“…MCs can also participate in bone destruction by promoting the release of proteases, histamine, TNF-a, IL-6, IL-11, IFN-g, RANKL, and other mediators. MCs increase the expression level of TNF-a, IL-1b, IL-6, IL-17, RANKL, and MMP-9 genes in response to IL-33 stimulation and stimulate human CD14+ monocytes to differentiate into TRAP-positive osteoclasts (83). Shin et al found that secretion of tryptase b by MCs was abundant in experimental models of arthritic mice, and the tryptase b/ heparin complex promoted FLS to express inflammationmediating neutrophil chemokines CXCL1/KC, CXCL5/LIX, and CXCL8/IL-8; additionally, tryptase b-deficient mice showed lower disease activity and bone destruction (84).…”
Section: Mast Cells a Novel Target For Treating Rheumatoid Arthritis Which Contributes To Therapeutic Heterogeneitymentioning
confidence: 99%